2020
DOI: 10.1159/000507716
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Autologous Topical Serum Based on Plasma Rich in Growth Factors Technology Counteracts Ultraviolet Light-Derived Photo-Oxidative Stress

Abstract: Introduction: Skin as the major barrier between the internal and external environments protects our body from external injuries. Ultraviolet B (UVB) radiation is majorly responsible for photoaging and is closely associated with oxidative stress, inflammation, and DNA damage. The progression in the field of biological therapies has led to the emergence of new autologous therapies based on growth factors. An autologous topical serum (ATS) based on the plasma rich in growth factors (PRGF) technology has also been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Results presented herein indicate that topical ES application on ulcerated models was able to maintain viable proliferating fibroblast levels and reduce both cell death and tissue damage. This could be related to previous reports that indicate the ability of ES to protect the skin from hostile microenvironments by reducing free radical accumulation and preventing DNA cleavage [29]. Enzymes like superoxide dismutase and catalase, with free radical scavenging activity, have been shown to be upregulated in response to autologous growth factors [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…Results presented herein indicate that topical ES application on ulcerated models was able to maintain viable proliferating fibroblast levels and reduce both cell death and tissue damage. This could be related to previous reports that indicate the ability of ES to protect the skin from hostile microenvironments by reducing free radical accumulation and preventing DNA cleavage [29]. Enzymes like superoxide dismutase and catalase, with free radical scavenging activity, have been shown to be upregulated in response to autologous growth factors [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…In addition, ES prevented DNA cleavage that occurs after solar exposure which is directly related to a decrease in tissue necrosis and cell apoptosis. 39 Moreover, it has been suggested that PRGF mediated photo-protection may be directly related to the activation of several antioxidant enzymes and the reduction of apoptotic caspases that ultimately maintain tissue viability. 40 , 41 Thus, hyperpigmented melanin spot reduction observed herein could be an additional effect of ES when counteracting solar photo-damage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important factor in the safety of plasma rich in growth factors. It has also a positive outcome minimizing the effect of the oxidative stress and reactive oxygen species on the cells, for example, by reducing the DNA double-strand cleavage [ 59 ]. Furthermore, it reduces the intensity of inflammation by the inhibition of transactivation of the transcription factor kappaB and the expression of COX2 (cyclooxygenase 2) and CXCR4 C-X-C (chemokine receptor type 4) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%